Non-biological reduction of Cr(vi) by reacting with humic acids composted from cattle manure. Issue 43 (23rd May 2017) - Wu, Min; Li, Gongxia; Jiang, Xiaolin; Xiao, Qianqian; Niu, Mingxing; Wang, Zhiyuan; Wang, Yayi
Abstract : Previous studies on reduction of Cr(vi ) by humic acids (HAs) have seldom used the extracts from composted animal manure. Abstract : Previous studies on reduction of Cr(vi ) by humic acids (HAs) have seldom used the extracts from composted animal manure. For greater yields of HAs and resource reclamation of animal manure, cattle manure was used as the composting material in our study. The capacity of humic acids extracted from composted cattle manure (HAscm ) to reduce Cr(vi ) was tested under the influence of environmental factors (pH, illumination with light and dissolved oxygen). And the non-biological detoxification mechanism was investigated by using three-dimensional fluorescence, Fourier transform infrared spectroscopy (FTIR) and X-ray absorption near-edge structure (XANES) spectroscopy. The results indicated that Cr(iii ) after the reduction of Cr(vi ) formed an outer sphere complex with –OH and inner sphere complex with carboxyl groups in HAscm .